Models of Interpersonal Trust Development: Theoretical Approaches, Empirical Evidence, and Future Directions - Lewicki, Roy J.; Tomlinson, Edward C.; Gillespie, Nicole (Journal of Management, 2006)
Most research on trust has taken a static, “snapshot” view; that is, it has approached trust as an independent, mediating, or dependent variable captured by measuring trust at a single point in time. Limited attention has been given to conceptualizing and measuring trust development over time within interpersonal relationships. The authors organize the existing work on trust development into four broad areas: the behavioral approach and three specific conceptualizations of the psychological approach (unidimensional, two-dimensional, and transformational models). They compare and contrast across these approaches and use this analysis to identify unanswered questions and formulate directions for future research.